A novel layer by layer energy efficient watchman algorithm for wireless sensor and actor networks - Draz, U. (Publishing House of the Romanian Academy, 2021)
In this paper, a novel layer-by-layer Energy Efficient Mobility-Based Watchman Algorithm (E2-MBWA) is introduced to increase the network lifetime by reducing the hotspot issue in wireless sensor and actor networks. Typically, WSAN networks are deployed to monitor physical objects or environmental conditions such as pressure, temperature, and sound, etc. Due to the high consumption of energy, nodes become dead early, these dead nodes cause to isolate some parts of the network. Therefore, the power management of such a network is highly complex. The limited power resources in the network are caused of the Hotspot problem. Due to the Hotspot issue in the network, limited network lifetime, unnecessary delay, data packet losses, throughput and end-to-end delay are mostly affected. Therefore, it is required to design a new algorithm that resolves these issues efficiently. In this approach, watchman nodes are introduced and sub-algorithm like the Watchman Nodes As-signing algorithm (WNAA). In addition, the proposed algorithm is provided alternative data storage (when a neighboring node of the sink is going to die) in the form of the Watchman Secondary Nodes Algorithm (WSNA). Energy consumption, end-to-end delay, and throughput are considered for the evaluation of the proposed algorithm. At the end, the proposed algorithm is compared with an existing state-of-the-art algorithm like the Efficient Traffic Load Reduction Algorithm (ETLRA) that also works with limbs node for the said problem in the same kind of wireless environment. Â© 2021, Publishing House of the Romanian Academy. All rights reserved.